Fostering Students’ Active Participation in Kitab Kuning Learning Through the Syawir Method in Islamic Boarding Schools - Ilmiyatul Husna; Achmad Mubarok; Wiwin Fachrudin Yusuf; Muhammada (Al-Qalam Institue, 2026)
This study aims to examine the implementation of the syawir method in improving students’ active participation in learning kitab kuning and to identify the supporting and inhibiting factors in its application. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving teachers and students in the Islamic boarding school environment. The findings revealed that the syawir method significantly enhanced students’ active participation during the learning process. Students became more engaged in asking questions, expressing opinions, participating in discussions, and understanding the learning material. Furthermore, the method created a more interactive and collaborative learning atmosphere among students. The implementation of the syawir method was supported by teacher guidance and students’ enthusiasm for learning, while differences in students’ levels of understanding and self-confidence became the main obstacles. The study implies that the syawir method can serve as an effective alternative learning strategy to promote active participation and collaborative learning in kitab kuning instruction.